Comparing Face-to-Face and Online Data Collection Methods in Preterm and Full-Term Children: An Exploratory Study - Nelson, Paige M.; Scheiber, Francesca; Laughlin, Haley M.; Demir-Lira, Ö. Ece (Frontiers in Psychology, 2021)
The COVID-19 pandemic has transformed the landscape for children’s daily lives and the landscape for developmental psychology research. Pandemic-related restrictions have also significantly disrupted the traditional face-to-face methods with which developmental scientists produce research. Over the past year, developmental scientists have published on the best practices for online data collection methods; however, existing studies do not provide empirical evidence comparing online methods to face-to-face methods. In this study, we examined performance on a battery of standardized and experimental cognitive assessments in a sample of 4- to 5-year-old preterm and full-term children, some of whom completed the battery face-to-face and some of whom completed the battery online. First, we asked how children’s performance differs between face-to-face and online format on tasks related to verbal comprehension, fluid reasoning, visual spatial, working memory, attention and executive functioning, social perception, and numerical skills. Our results suggested that scores did not differ on the majority of the neurocognitive assessments that were administered, with the exception of a few subtests. Second, we explored the role of parent involvement in children’s performance in the online format. We did not find a significant effect of parent involvement on children’s performance. Our findings contribute to the growing body of literature examining differences and similarities across various data collection methods, as well literature surrounding online data collection for continuing developmental psychology research.